Dynamic strength of the quadriceps muscle and sports activity - Hahn, T.; Foldspang, A.; Ingemann-Hansen, T. (British Journal of Sports Medicine, 1999)
The study objectives were to examine the dynamic strength of the quadriceps muscle in athletes, and investigate its association with participation in sport. The study comprised 168 active competitive non-pregnant athletes, aged 14-24 years. The dynamic strength of their quadriceps muscle was measured, and they answered a questionnaire about sports activity and occupation. The dynamic strength of the quadriceps muscle was significantly higher in men than in women, and was positively associated with body weight, years of jogging, years of soccer, and weekly hours of basketball. In conclusion, the dynamic strength of the quadriceps muscle seems to be associated with sports activity. The results suggest sport specific adaptation, which may reflect high levels of running and jumping activity.